Features of food design on a 3D printer. A review - E. V. Ulrikh; V. V. Verkhoturov (Пищевые системы)
3D printing technology attracts considerable attention due to its versatility and possibility of using in different industries such as the aerospace industry, electronics, architecture, medicine and food industry. In the food industry, this innovative technology is called food design. 3D printing is a technology of additive manufacturing, which can help the food industry in the development of new and more complex food products and potentially help manufacture products adapted to specific needs. As a technology that create foods layer by layer, 3D printing can present a new methodology for creating realistic food textures by precise placement of structuring elements in foods, food printing from several materials and design of complex internal structures. In addition to appearance and taste, food consistency is an important factor of acceptability for consumers. The elderly and people with dysphagia not infrequently suffer from undernutrition due to visual or textual unattractiveness of foods. The aim of this review is to study the available literature on 3D printing and assess recent developments in food design technologies. This review considers available studies on 3D food printing and recent developments in food texture design. Advantages and limitations of 3D printing in the food industry, possibilities of printing based on materials and consistency based on models as well as future trends in 3D printing including technologies of food preparation by printing on food printers are discussed. In addition, key problems that prevent mass introduction of 3D printing are examined in detail.